Effects of the clearance between the core plate and restraining part on the structural performance of the buckling‐restrained brace using steel mortar planks. Issue 1 (3rd February 2022) - Fujita, Masanori; Nakamura, Makoto; Awazu, Kengo; Iwata, Mamoru
Abstract: The clearance between the core plate and the restraining part of the buckling‐restrained brace using steel mortar planks (BRBSM) considerably affects the failure mode and hysteretic characteristics of the brace. A clearance adjustment construction is proposed for the BRBSM which can control the clearance through partially pasting clearance adjustment materials and polishing the mortar plank surface. First, the clearance adjustment construction workflow and quality control are demonstrated, and it is verified that the clearance can be assured by fabricating specimens. Further, the effects of the difference in clearance between the core plate and restraining part on the structural performance of the BRBSM in terms of failure behaviour, increase strength ratio, buckling mode and cumulative plastic strain energy ratio are evaluated by conducting a cyclic axial loading test.